Prevalence of Hypothyroidism in Peri-/Post-Menopausal Thai Women - Kanokphon Butmarasri; Sukree Soontrapa; Srinaree Kaewrudee; Charoonsak Somboonporn; Woraluck Somboonporn (The Royal Thai College of Obstetricians and Gynaecologists, 2017)
Objectives: This study aimed to determine the prevalence of hypothyroidism and its association with menopausal symptoms and evaluated the diagnostic performance of Zulewski's clinical score for predicting hypothyroidism in peri-/post-menopausal Thai women. Materials and Methods: This hospital-based cross-sectional study was conducted between June 2015 and April 2016 in Srinagarind Hospital, Khon Kaen, Thailand. We enrolled 305 peri-/post- menopausal women 45-65 years of age without previous history of thyroid diseases, radiation exposure at the neck, or concurrent use of lithium. The participants were interviewed by two research assistants' vis-à-vis symptoms of menopause and hypothyroidism, current medications and menstrual characteristics. Blood samples were taken for TSH and FT4 levels. Main outcomes were prevalence of hypothyroidism, the Menopause-Specific Quality of Life (MENQOL) score, and diagnostic performance of Zulewski's clinical score . results: Mean age was 56 ± 4.7 years. The prevalence of hypothyroidism was 6.2% (95%CI 3.5% to 8.9%). The sensitivity of Zulewski's clinical score at the cutoff point ≥ 3 was 70%. Neither the MENQOL domain score nor the composite score was associated with hypothyroidism. Conclusion: The prevalence of hypothyroidism in peri-/post-menopausal Thai women is low. There is no association between MENQOL score and hypothyroidism. Zulewski's clinical score is not a good screening test for hypothyroidism in this group.